Do You Hear More Piano or Drum Sounds? An Auditory Version of the Solitaire Illusion. (December 2016) - Prpic, Valter; Luccio, Riccardo
The solitaire illusion is an illusion of numerosity proposed by Frith and Frith. In the original version, an apparent number of elements was determined by the spatial arrangement of two kinds of elements (black and white marbles). In our study, an auditory version of the solitaire illusion was demonstrated. Participants were asked to judge if they perceived more drum or piano sounds. When half of the piano tones were perceived as lower in pitch than a drum sound and the other half higher, piano tones appeared to be arranged in small units, leading to numerosity underestimation. Conversely, when all piano tones were perceived to be higher in pitch than the drum sounds, they appeared to be arranged in a single large unit, leading to numerosity overestimation. Comparable to the visual version of the solitaire illusion, the clustering seems to be determined by Gestalt principles. In our auditory version, a clear reversal of the illusion (numerosity overestimation or underestimation) was observed when piano tones appeared to be arranged in a single large cluster or in several small clusters, respectively.